Tracing the Trajectory in Acquisition of Graphic Skill to Students Through Creative Sorting Game - Odewumi, Michael Olubunmi (FKIP Universitas Lampung, 2019)
Educators have been striving to bring to reality learning through playing and fun. It is real obvious that the use of game has brought positive changes to instruction. Therefore, this study investigates the acquisition of graphic skill through creative sorting game among the junior secondary schools. The study employed experimental of pre and post test from quasi, samplings consisted of 69 students of which are 34 male and 35 female students, based on simple random sampling. Two hypotheses were raised and tested with ANOVA and t-test statistical analysis. Findings revealed that creative sorting game was positive in the context of teaching creative arts and it was recommended that the use of creative sorting game should be encouraged in learning among the junior secondary schools in Nigeria.Keywords: creative sorting game, graphical skills, junior high school, quasi experimental design DOI: http://dx.doi.org/10.23960/jpmipa/v20i2.pp30-38